The revenant: rediscovery of Margaritifera homsensis from Orontes drainage with remarks on its taxonomic status and conservation (Bivalvia: Margaritiferidae). Issue 1 (2nd January 2018) - Vikhrev, Ilya V.; Bolotov, Ivan N.; Altun, Ayhan; Gofarov, Mikhail Y.; Dvoryankin, Gennady A.; Kondakov, Alexander V.; Ozcan, Tahir; Ozcan, Gulnaz
Abstract : Since Margaritifera marocana (Pallary, 1918) and M. laosensis (Lea, 1863) were rediscovered, M. homsensis (Lea, 1865) remains the only pearl mussel species known solely based on old shell samples from natural history museums. This is also the last pearl mussel species, which is absent in a phylogeny of the family. Here, we aimed to provide an integrative revision of the taxonomic status of M. homsensis from the Orontes Basin. Using a newly collected specimen from the River Karasu, Hatay Province, southern Turkey, five gene partitions were sequenced, the cytochrome c oxidase subunit I (COI), large ribosomal subunit rRNA (16S), large ribosomal subunit rDNA (28S) and its D3 expansion segment (D3), and small ribosomal subunit rDNA (18S). The multi-gene phylogeny indicates that M. homsensis is a sister taxon of M. auricularia, but both these species are closely related to M. marocana by nuclear genes. The main conchological features, i.e ., the shell shape, teeth morphology, and mantle attachment scars, as well as Fourier shell shape analysis have not shown principal differences between M. homsensis and M. auricularia . Based on these data, we concluded that M. homsensis is a valid species that is most closely related to M. auricularia . Special conservation efforts for a population of M. homsensis discovered in Turkey, including the formation of a nature reserve, might contribute to the conservation of the species. Finally, an extensive search for surviving populations in Orontes drainage (southern Turkey, Lebanon, and Syria) and the Nahr-el-Kabir River (Lebanon and Syria) remains necessary to develop a transboundary conservation strategy for this unique taxon.